The Use of Translation Techniques for Translation of Post -Modifier Noun Phrases in “The Frog Prince” Subtitles by EFL Learners - Iswandi, Fedro; Sahronih, Siti; Utami Durahman, Eva (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2024)
This research aims to identify the structure of post-modifier noun phrases and analyze translation techniques of post-modifier noun phrases in ‘The Frog Prince’ subtitles that translated by EFL learners. This research is a descriptive qualitative method to compare the uses of translation techniques of post-modifier noun phrases translation between A class students and B class students of English Literature at STIBA Invada.  This research used the theory of post-modifier noun phrases based on Aarts (2001) and translation techniques are proposed by Molina & Albir (2002). Then, the technique of collecting data is document analysis. The findings of this research show that there are 4 data of post-modifier noun phrases found in ‘The Frog Prince’ subtitles. Next, there are 4 translation techniques are applied by the A class students and B class student including established equivalent, adaptation, discursive creation, and reduction generally. It can be concluded that translation techniques that we chose between A class student and B class students can influence the meaning and form (structure) of post-modifier noun phrase from source language into target language.